MARINE MICROORGANISMS AS A SOURCE OF NEW ANTIBIOTICS - MUMINOVA, ZIYODA; HUSSEYN, MUHAMED; MUTALLIYEVICH, DEDAKHANOV ABDUMALIK; KARTHIK, K.; NANDA, MR. NAIMISH (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Infections in animals, including humans, are caused by microorganisms. Antimicrobial drugs are typically used to treat infections. These antimicrobial substances can originate from microbes, plants, and animals. Antimicrobial agents, sometimes known as antibiotics, are produced in large part by microorganisms. Antibiotics can be synthetic, natural, or semi-synthetic substances. Microorganisms produce natural antibiotics. Nearly two-thirds of all known antibiotics with a microbial origin come from actinomycetes. More than 6000 molecules are produced by Streptomyces species, some of which are significant pharmaceuticals that are traded on the market and utilized as immunosuppressive, anti-infective, or anti-cancer medications. Numerous physiologically active metabolites can be produced by bacteria. Some of them may be insecticides, herbicides, or enzymes like xylanase and cellulase, while others are antibiotics. Numerous industries make use of them. Antibiotics are the most widely used of these substances in medicine and have significant economic value. Numerous industries, including medicines, animal husbandry, and agriculture, have made use of antibiotics. Scientists around the world have been actively pursuing the screening of microbes for the development of antibiotics for decades.